THE OIL VENTURE–AN EXERCISE IN ACCOUNTING. - Woods, L. Milton (The Accounting Review, 1958)
The great risks which are inherent in the oil exploration effort make desirable some organization which will spread these risks. Also conservation requirements often dictate organizations which extend beyond existing ownership patterns in a given field development. These factors give the oil venture a characteristic not found in most other ventures. The parties to the oil venture are often very unequal in terms of economic size. The great giants of the industry are found joined in ventures with small corporations, partnerships, and even individuals. This is the primary reasons that there is almost no standardization between ventures, for each situation is different from every other. This tends to create some interesting problems for the accountant who has to maintain proper records of the many, and often complicated transactions arising from the venture. However, cost is difficult to define, especially when one is dealing with used materials, so that its value is almost lost in some cases. Also, there is no uniformity of depreciation rates in the industry, so that "net book value" is meaningless. And probably most important, any effort to utilize cost would make auditing extremely difficult, since it would require the maintenance of original detail long after most companies would dispose of it.